Microtubule Reorganization during Mitosis and Cytokinesis: Lessons Learned from Developing Microgametophytes in Arabidopsis Thaliana - Liu, Bo; Ho, Chin-Min K.; Lee, Yuh-Ru J. (Frontiers in Plant Science, 2011)
In angiosperms, mitosis and cytokinesis take place in the absence of structurally defined microtubule-organizing centers and the underlying mechanisms are largely unknown. In the spindle and phragmoplast, microtubule reorganization depends on microtubule-interacting factors like the γ-tubulin complex. Because of their critical functions in cell division, loss-of-function mutations in the corresponding genes are often homozygous or sporophytic lethal. However, a number of mutations like gem1, gcp2, and nedd1 can be maintained in heterozygous mutants in Arabidopsis thaliana. When mutant microspores produced by a heterozygous parent undergo pollen mitosis I, they are amenable for phenotypic characterization by fluorescence microscopy. The results would allow us to pinpoint at specific functions of particular proteins in microtubule reorganization that are characteristic to specific stages of mitosis and cytokinesis. Conclusions made in the developing microgametophytes can be extrapolated to somatic cells regarding mechanisms that regulate nuclear migration, spindle pole formation, phragmoplast assembly, and cell division plane determination.